Behavioural science principles for scaling-up zero tillage wheat and maize in the Eastern Terai region of Nepal - Ghimire, Yuga N.; Timsina, Krishna P.; Adhikari, Surya P.; Shrestha, Keshav P.; Gairhe, Samaya; Acharya, Yogendra; Devkota, Deepa; Upadhyay, Namdev; Kharel, Meena; Poudel, Hema K.; Prior, Roy M.; Rola-Rubzen, Maria Fay (Journal of Agriculture and Natural Resources, 2021)
Farmers have a set of convictions and tend to do what their forefathers had practiced. By identifying their beliefs and designing appropriate ways of upscaling to convince them of new and improved practices, we can improve the adoption of zero tillage technology for maize and wheat. Small and fragmented landholdings that resulted from the cultural system of distributing land to heirs are diverse in their cropping requirements. Moreover, farmers are risk-averse and do not believe easily in new technologies. Traditional extension approaches have not been effective in upscaling these technologies. A new way of thinking based on behavioural science can provide some insights and guidelines for improving the effectiveness of technology adoption. Understanding farmers' socioeconomic circumstances and their decision-making system at the household and society level can help in designing upscaling approaches. Approaches such as capitalising on social bonding, use of established technology leaders, and use of farmers' organizations can improve adoption. Recommended strategies include encouraging a comprehensive contracting system of service provision, using active community influential local leaders in technology expansion, taking group and social identity approaches in technology extension, and capacity building programs for service providers/operators and farmers to help raise confidence and to remove perceived barriers to technology adoption.